EXAMINATION IN AUDITING. - Meigs, Walter B.; Larsen, E. John (The Accounting Review, 1964)
The article presents questions of the auditing section of the American Institute of Certified Public Accountants (CPA) examination. It informs that when no audit has been performed, any financial statements with which a CPA's name is associated should be conspicuously marked on each page as unaudited.